2016
DOI: 10.1097/bpo.0000000000000482
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Pediatric and Adolescent Anterior Cruciate Ligament Injury and Reconstruction

Abstract: Level III-retrospective cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
191
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(204 citation statements)
references
References 30 publications
8
191
1
4
Order By: Relevance
“…These findings support those of studies in other countries, such as the USA, that the rate of ACL injuries in pediatrics and adolescents is increasing [2,7,14,24]. Previous research has reported an increase in the rate of hospital-treated sports injuries in children in the same geographic region over the same period [25].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…These findings support those of studies in other countries, such as the USA, that the rate of ACL injuries in pediatrics and adolescents is increasing [2,7,14,24]. Previous research has reported an increase in the rate of hospital-treated sports injuries in children in the same geographic region over the same period [25].…”
Section: Discussionsupporting
confidence: 88%
“…For example, studies in the late 1970s and early 1980s reported the incidence of ACL rupture in skeletally immature individuals sustaining a knee injury as being between 1.0% and 3.4% [9,10,11,12]. However, as imaging and clinical awareness of injuries in young athletes has improved, the diagnosis and reported incidence of ACL injury in the skeletally immature population has increased [13], and ACL tears in pediatric and adolescent patients are no longer considered rare [7,14]. Whilst it is possible that improved methods of diagnosis are responsible for greater rates of reconstruction, or that reconstruction rates have increased due to improved methods of treatment in the skeletally immature, it is also possible that the incidence of ACL tears is truly increasing in children and adolescents [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A separate analysis that queried a national database showed that from 2007 to 2011 there was a 19 % increase in the number of This article is part of the Topical Collection on Pediatric Orthopedics ACL tears diagnosed in the 10-to 14-year age group and a 28 % increase in ACL reconstruction. The study also revealed that diagnosis and reconstruction of pediatric ACL tears were rising at a rate significantly higher than that of adults [12]. These numbers were similar to that seen in a populationbased study from New York State that revealed that the rate of ACL reconstructions over the last 20 years has more than doubled in patients aged 3 to 20 years [13].…”
Section: Incidencesupporting
confidence: 70%